An ANALYSIS OF STUDENT SELF-CONFIDENCE PRACTICE IN PUBLIC SPEAKING AT THE TENTH GRADE ICT MAJOR OF SMK CANDA BHIRAWA PARE - Dewi , Fatqu Rofiqoh; Sistiani, Liana; Dewi, Novi Rina (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
Every student must be confident in public speaking. Without confidence, we cannot communicate our ideas to the public. One of the successes in learning English can be measured by proficiency in English language skills. Confidence in speaking English needs to be improved again, practice every day so that confidence in speaking English is always changing and can be improved. The researchers of this study are currently analyzing the student self-confidence practice in public speaking at the tenth grade of ICT major of SMK Canda Bhirawa Pare. This research used qualitative research method. This qualitative research method was conducted through four instruments. They were as follows: (1) Observation (2) Interview (3) Questionnaire (4) Documentation. The result of this research is to know the strategy the teacher to build self-confident and the students’ responses toward self-confidence at SMK Canda Bhirawa Pare. The research result showed that the students of SMK Canda Bhirawa showed that some students lack confidence when speaking in public, which is determined based on data from teachers and direct observations from the author. Researcher asked about students' responses self-confidence, and students also have a high negative thought, do not believe in their abilities and are always pessimistic.